Pelatihan Kepemanduan di Desa Wisata Donokerto - Setiaji, Yudi; Wahyono, Mohammad Hardi; Santosa, Santosa (Sekolah Tinggi Pariwisata AMPTA, 2020)
Donokerto village is one of the pioneering tourist villages that has good potential in terms of diversity of tourist attractions. As a Pioneer tourism village, the village of Donokerto requires qualified human resources for tourism services, especially as a tour guide. Therefore, the AMPTA Yogyakarta Tourism School in collaboration with PUM Netherlands Senior Experts held a community service with the theme